Application of solar induced ventilation prototype in Small and Medium Enterprise (SME) building - Sapian, Abdul Razak; Mohammad Yusoff, Wardah Fatimah; Adam, Nor Mariah; Salleh, Elias (2012)

(untitled)
The research presents the investigation on the application of solar induced ventilation prototype in industrial building, particularly the premises of small and medium enterprises (SMEs). The application of this strategy in SME premises is expected to promote natural ventilation, hence reducing the business operating cost. Moreover, high ventilation rates are necessary to such building in maintaining healthy indoor air quality. The performance of the proposed solar induced ventilation is evaluated based on four variables, namely air temperature, air velocity, mass flow rate and air flow rate. The investigations of air flow rate and air temperature inside the single storey SME building are limited to the indoor working area only. Further enhancement of the prototype performance in increasing air flow rate and reducing air temperature at the indoor working area of the SME building is limited to the width investigations only. The methodology applied is Computational Fluid Dynamic (CFD) modeling. The application of the prototype at the SME building is able to enhance air flow rate and reduce air temperature at the indoor working area. The highest air temperature reduction attained by the enhancement from 1 meter to 4 meter width solar collector is 1.3 ºC. Meanwhile, the highest air flow rate increment achieved for the enhancement from 1 meter to 4 meter width is 0.24 m³/s.